Baroque Ethos in Borges: Resistance and Creation - Pérez Bernal, Ángeles Ma. del Rosario (2022)
Jorge Luis Borges' essays on Walt Whitman (“The Other Whitman,” “Note on Walt Whitman”) and on Gustave Flaubert (“Flaubert and His Exemplary Destiny”) are inserted into the Baroque trend as Latin American aesthetics via two processes that illustrate its ethos: resistance and creation. Borges finds his reflection in the figures of Whitman and Flaubert for an anamorphic becoming-other.